IDENTIFIKASI VARIASI GENETIK KERBAU LOKAL JAWA TIMUR (Bubalus bubalis) DARI WILAYAH YANG BERBEDA BERBASIS MIKROSATELIT - Riyanto Riyanto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2015)
This study aims to determine: 1) the variation of the local buffalo phenotype in East Java from the Banyuwangi and Blitar regions; and 2) genotypes of local buffalo-based genotypes in East Java from the Banyuwangi and Blitar regions. Observation of genetic variation patterns was carried out starting from the stages of DNA isolation followed by electrophoresis using agarose gel after PCR was carried out and followed by polyacrylamide gel electrophoresis. From this gel electrophoresis, a band was obtained which was then analyzed using Genepop ver. 3.1d. The results of the analysis show that the genetic variation of Blitar buffalo population is higher when compared to the Banyuwangi buffalo population. This can be seen from the average value of allele polymorphic information in the Blitar buffalo population of 55% while the average value of polymorphic information in the Banyuwangi buffalo population is 47%. The allele frequency values of the three microsatellite loci of Blitar buffalo population ranged from 0.06 to 0.65, while the allele frequency values of the three microsatellite loci of the Banyuwangi buffalo population ranged from 0.07 to 0.63, after the allele frequency values were known, the analysis continued with determination heterozygosity value. The average value of heterosigosity in the Blitar buffalo population of the three loci is 41.50%, while the average value of heterosigosity of the Banyuwangi buffalo population is the third locus of 27.60%. This figure shows that the average value of heterosigosity in the Blitar buffalo population is higher when compared with the average value of heterozygosity in the Banyuwangi buffalo population.